PROJECT-BASED LEARNING AND 21ST-CENTURY SKILLS: DEVELOPING CRITICAL THINKING AND COLLABORATION IN PRIMARY CLASSROOMS - Huda Al-Shawabkeh; Bassam Al-Khouri; Salma Hamdan; Ida Aulia Mawaddah (International Journal of Educatio Elementaria and Psychologia, 2026)
Project-Based Learning has gained increasing attention as an instructional approach aligned with the demands of twenty-first-century education, particularly in fostering higher-order thinking and social competencies in primary classrooms. This study aims to examine the effectiveness of Project-Based Learning in developing critical thinking and collaboration skills among primary school students. The research employed a quasi-experimental mixed-methods design involving an experimental group taught through Project-Based Learning and a comparison group receiving conventional instruction. Quantitative data were collected through performance-based critical thinking tests and collaboration observation rubrics, while qualitative data were obtained from classroom observations and teacher field notes. The results indicate that students exposed to Project-Based Learning demonstrated significantly higher gains in critical thinking and collaboration than those in the comparison group. Qualitative findings further revealed improved student engagement, more balanced participation, and deeper peer interaction during project activities. The study concludes that Project-Based Learning provides an effective pedagogical framework for integrating cognitive and social skill development in primary education. These findings suggest that early implementation of learner-centered, inquiry-based instruction can support the cultivation of essential twenty-first-century skills without compromising curricular objectives. The implications extend to teachers, curriculum designers, and policymakers seeking evidence-based strategies for meaningful primary classroom innovation worldwide contexts.